Научно-инженерное моделирование процессов переработки нефти и газа; Деловой журнал Neftegaz.RU; №6 (150) - Боев А. С. Артем Сергеевич; Ивашкина Е. Н. Елена Николаевна; Чузлов В. А. Вячеслав Алексеевич; Долганов И. М. Игорь Михайлович; Назарова Г. Ю. Галина Юрьевна (2024, 2024)
Заглавие с экрана